Green Human Resource Management in Cosmos Technology Limited Liability Company - Vinh, Luu The (Journal of Ecohumanism, 2024)
Green human resource management (GHRM) increasingly plays an important role in enterprises' sustainable development strategies. This topic has been initially studied in Vietnam, but not many enterprises have applied it. The purpose of this article is to clarify the content of green human resource management and green human resource management practices at COSMOS Technology Limited Liability Company in the following aspects: Green job design and analysis; green recruitment; green training and development; green performance management; green compensation and discipline; green labor management. Thereby, helping to orient enterprises in the application process, and at the same time suggesting further research on green human resource management in Vietnam.